PROBLEMATIKA PENUTUR NON ARAB DALAM PEMBELAJARAN BAHASA ARAB - Zainudin, Udin (Program Studi Pendidikan Agama Islam, 2023)
The background of this research is that there are still students who have morals that do not yet reflect that they are students who have received a lot of religious knowledge, both from ustadz and ustadzah who are carried away by their bad habits before they entered the Raudlatul Mutaalimin Islamic boarding school, Cilendek, Tasikmalaya City. For example, there are still students who violate the rules and are negligent when doing the 5 daily prayers, are lazy when doing activities in the dormitory, there are still students who have a harsh attitude so they cannot understand friends in their environment, there are still students who feel normal when doing a deed that is not good even there are some students who still dare to steal other people's belongings. This type of research is qualitative research conducted with data collection techniques: observation, interviews and documentation. Data analysis techniques: Data reduction, data display and draw conclusions. The subjects in this study were Ustadz/Ustadzah and 10 students from the Raudlatul Mutaalimin Cilendek Islamic boarding school. mThe research results achieved in this study can be seen that in improving the character of the mutawasith class students at the Raudlatul Mutaalimin Cilendek Islamic Boarding School, namely by having several programs that must be carried out by all students including, Exemplary, Routine Memorization, Muballighin wa Muballighah and Gebyar Ma'had. Then there are also rules that must be obeyed by all students. While the factors that inhibit the improvement of the character of the students at the Raudlatul Mutaalimin Cilendek Islamic boarding school are psychological factors and educational factors, namely regarding the religious understanding of the students. Furthermore, the application of the Tarbiyatul Muballighin wa Muballighah method at the Raudlatul Mutaalimin Islamic Boarding School is by holding a competition between the students who are included in the competition, namely Speech, MQK, Khutbah, Tahfidz, Reasoning Haflan Matan. Then each competition will be divided into 3 rounds namely the preliminary round, semifinal round and grand final round.